Attitudes towards tooth fillings in Tanzanian adults and its association with previous filling experience - Nyamuryekung'e KK; Lahti SM; Tuominen RJ (BIOMED CENTRAL LTD, 2022)
Background: Tooth filling treatment is utilized at low levels in many low and middle-income countries (LMICs), further, little is known about the prevailing attitudes towards such treatment. This study aimed to assess attitudes towards tooth filling among Tanzanian adults and how previous tooth filling experience is associated with these attitudes.Methods: A pretested structured questionnaire was distributed among 1522 out-patients in four regional hospitals in Tanzania in 2015-16. The questionnaire had eight statements on a 6-point Likert scale measuring attitudes towards tooth filling. Responses were analyzed independently and through a constructed attitude sum score. Linear regression analysis was used to assess the association of previous tooth fillings on attitudes towards tooth filling treatment.Results: The respondents were mostly female (57.3%), with a mean age of 33.1 years (SD 11.3). About one third of the respondents (36.4%) had primary level of education. Attitudes towards tooth filling treatment were generally negative. Low levels of education and income were associated with more negative attitudes. A small proportion (11.5%) had a previous tooth filling. Having a previous tooth filling was associated with a more positive attitude towards tooth fillings regardless of socioeconomic status.Conclusions: This study shows that even in areas with limited resources and availability of services, previous experience of tooth fillings is related to more positive attitudes towards restorative treatment, which should be taken into account when planning oral health care programs.